Gastropoda Mangrove dari Pulau Lombok, Nusa Tenggara Barat - Nova Mujiono, (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Mangrove Gastropods from Lombok Island, West Nusa Tenggara. Mangrove forest in Lombok island covers an area of 3,305 ha; an area of 1,643 ha (49.7%) is still in good condition and the remaining 1,662 ha (50.3%) is in damaged condition. The damaged mangrove will impact on the decline of fauna biodiversity. This research was conducted in April 2015 and aimed to determine the composition and distribution of mangrove mollusks, especially gastropods, in Lombok Island. The method used is purposive sampling and visual encounter. Observations were carried out at six stations. A total of 1,236 specimens have been collected, consisting of 11 families and 31 species. Species composition ranged 5–13 species for each station. Gastropod species composition was influenced by physical environmental conditions of mangrove forest. Chicoreus capucinus was the only carnivorous gastropod found in this location and Haminoea tenera (Haminoeidae) was a new record for Indonesia.